Penerapan Problem Based Learning Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Pembelajaran Tematik - Anita Desy Ratnasari; Wahyudi Wahyudi; Intan Permana (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The purpose of this Classroom Action Research (CAR) is to improve students’ learning outcomes in thematic learning by using the Problem-based Learning. The model used for the research of Stringer ET uses the steps look, think, act, while the technique used for data collection is using observation techniques. The instrument in this study was an observation sheet. This Classroom Action Research (CAR) was conducted in 2 cycles. From the results of the actions taken, it is proven that Problem-based Learning can improve student learning outcomes. The learning outcomes obtained are, the average learning outcomes for the class are 52.00 (pre-cycle), 61.00 (cycle 1), and 82.00 (cycle 2) and the completeness of the KKM in the class reaches 85%. The results of this Classroom Action Research show that the Problem-based Learning can improve students’ learning outcomes in thematic learning in class III SD Negeri Gondoriyo, Jambu District, Semarang Regency.